Effect of ibuprofen on muscle, hematological and renal function, hydric balance, pain, and performance during intense long-distance running - de Souza, R. F.; de Matos, D. G.; Ferreira, A. R. P.; Chilibeck, P.; de Almeida Barros, N.; Oliveira, A. S.; Cercato, L. M.; da Silva, D. S.; Aidar, F. J. (The Journal of Strength and Conditioning Research, 2020)
The aim of this study was to investigate the effect of prophylactic use of nonsteroidal anti-inflammatory drugs (i.e., ibuprofen) on physical performance, vertical jump, muscle biomarkers, liver, kidney, acute pain, and hydration status of participants in the 42-km Trail Running Challenge, a long-distance race integrated over mountain routes. The sample consisted of 20 men randomly divided into 2 groups: a control group (CG) and an experimental group (EG), with 12 completing the race (41.1 ± 8.8 years; 75.7 ± 12.1 kg) and included in the final analysis. The EG were administered an ibuprofen capsule (400 mg) 15 minutes before the beginning of the race and again after 5 hours of racing if the route was not yet completed. There were significant time main effects for creatine kinase (p = 0.001; f2 Cohen = 0.25), lactate dehydrogenase (p < 0.001; f2 Cohen = 2.05), aspartate aminotransferase (p = 0.002; f2 Cohen = 1.53), creatinine (p = 0.002; f2 Cohen = 2.24), urea (p = 0.001; f2 Cohen = 2.25), heart rate (p < 0.001; f2 Cohen = 4.88), and pain scores (p < 0.001; f2 Cohen = 1.93) all of which increased during the race. There was a group × time interaction for squat jump, which significantly decreased only in the CG (p = 0.045; f2 Cohen = 2.17). This may have been related to increased frequency of pain reported after the race in the gastrocnemius of the CG compared with the EG (p = 0.05). It was concluded that ibuprofen intake did not reduce muscle damage during the competition but maintained leg muscular power performance (i.e., vertical jump), possibly by reducing gastrocnemius muscle pain.